2007
DOI: 10.1007/s00441-007-0546-8
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells and neonatal brain injury

Abstract: Recent advances in regenerative medicine and in our understanding of neurogenesis may lead to new ways of recovering neuronal function lost or damaged during the perinatal period; such injuries are not amenable to conventional therapies. We review recent experimental studies based on immature rodental models of neonatal brain injury, especially hypoxic-ischemic encephalopathy. The developing brain is revealed to have considerable potential with respect to proliferation and migration to the injured site. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Considering that cell migration plays an important role in the injury-induced neurogenesis and tissue regeneration [ 13 , 14 ] . For example, progenitor cells from periventricular region proliferate and migrate into the hippocampus to regenerate new neurones after ischemia and reduce neurological deficits in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…Considering that cell migration plays an important role in the injury-induced neurogenesis and tissue regeneration [ 13 , 14 ] . For example, progenitor cells from periventricular region proliferate and migrate into the hippocampus to regenerate new neurones after ischemia and reduce neurological deficits in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence has indicated that periostin is a neurite outgrowth-promoting factor. Periostin promotes the proliferation and differentiation of neural stem cells in the brain after ischaemic or haemorrhagic injury 19 , which may rescue neuronal loss and restore brain function 20 . An injection of periostin into the lateral ventricles of hypoxic-ischaemic rats was recently shown to significantly improve spatial learning and memory, indicating that periostin may reverse cognitive deficits after IS 19 .…”
Section: Discussionmentioning
confidence: 99%
“…An article by Ikeda (2007) describes recent experimental results, including data from his laboratory, regarding neuronal stem cells and neonatal brain damage. The review focuses on hypoxic-ischemic brain injury as a model of neonatal brain injury, which is considered as one of the optimal candidates for regenerative therapy.…”
Section: Neural Stem Cellsmentioning
confidence: 97%